Expression, Role, and Regulation of Neutrophil Fcγ Receptors - Wang, Yu; Jönsson, Friederike (Frontiers in Immunology, 2019)
Neutrophils are best known for their critical role in host defense, for which they utilize multiple innate immune mechanisms, including microbe-associated pattern recognition, phagocytosis, production of reactive oxygen species, and the release of potent proteases, mediators, antimicrobials, and neutrophil extracellular traps. Beyond their well-established contribution to innate immunity, neutrophils were more recently reported to interact with various other cells, including cells from the adaptive immune system, thereby enabling them to tune the overall immune response of the host. Neutrophils express different receptors for IgG antibodies (Fcγ receptors), which facilitate the engulfment of IgG-opsonized microbes and trigger cell activation upon crosslinking of several receptors. Indeed, FcγRs (via IgG antibodies) confer neutrophils with a key feature of adaptive immunity: an antigen-specific cell response. This review summarizes the expression and function of FcγRs on human neutrophils in health and disease, and how they are affected by polymorphisms in the FCGR loci. Additionally, we will discuss the role of neutrophils in providing help to marginal zone B cells for the production of antibodies, which in turn may trigger neutrophil effector functions when engaging FcγRs.